Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Metal-free activation of peroxymonosulfate by natural organic acid or inorganic acid for wastewater disinfection and emerging contaminants degradation - Ying Liu; Jingfeng Gao; Yameng Wang; Yan Guo; Yi Zhang (Chemical Engineering Journal, 2026)

Electrostatic shielding and metabolic interplay in microbial defense: Unraveling the dual stress responses of nitrification-anammox systems to per/polyfluoroalkyl substances and quaternary ammonium compounds - Hanyi Wang; Jingfeng Gao; Zhiqi Wang; Yuxuan Wang; Yi Guo; Hongxin Xu (Journal of Hazardous Materials, 2026)

Masked ecological risk: Stable anammox performance conceals resistance genes propagation under short-term non-antibiotic antimicrobials stress - Qiyue Zuo; Jingfeng Gao; Jinming Zhang; Tianyi Lu; Ke Zhang; Ke Li; Feifei Gao; Yameng Wang; Yan Guo (Bioresource Technology, 2026)

Plastisphere enhanced resistance genes propagation in sulfur autotrophic/heterotrophic denitrification system under mixed quaternary ammonium compounds pressure - Yuxuan Wang; Jingfeng Gao; Zhiqi Wang; Hanyi Wang; Yi Guo; Jinming Zhang (Bioresource Technology, 2026)

The merits of novel partial nitrification inhibitors: Enhancing nitrogen removal performance while suppressing the spread of resistance genes in partial nitrification-anammox system - Tian Xie; Jingfeng Gao; Yi Zhang; Yi Guo; Hanyi Wang; Jinming Zhang (Journal of Hazardous Materials, 2026)

A coupled rockfall-bridge damage assessment method integrating trajectory simulation and intrusion detection - Jingfeng Zhang; Jie Ma; Jizhuang Guo; Jiaxin Luo; Han Bao; Huaimao Yang (Engineering Structures, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Dual-mode regulation of cyclohexylamine biodegradation by dissolved oxygen: Metabolic trade-offs and community stability mechanisms - Cheng Qiu; Jingfeng Ding; Minwen Guo; Can Chen; Wenwu Zhang; Bin Yang; Yang Hou; Zhongjian Li (Journal of Water Process Engineering, 2026)

Distinct influence of preservatives on microbial community and resistance gene in bio-carriers biofilm and microplastics biofilm as revealed in sulfur autotrophic denitrification coupled with anammox system - Ke Zhang; Jingfeng Gao; Yi Guo; Tian Xie; Yi Zhang; Jinming Zhang; Tianyi Lu (Environmental Research, 2026)

Experimental study on punching shear performance of embedded special-shaped CFST column base - Yong Liu; Zhuofei Li; Jingfeng Wang; Lanhui Guo; Fan Ye; Shasha Tan; Beibei Li (Engineering Structures, 2026)

Influences of Structural and Species Diversity on Forest Resistance to Drought - Erin T. H. Crockett; Qinfeng Guo; Jeff W. Atkins; Ge Sun; Kevin M. Potter; Jennifer K. Costanza; Scott V. Ollinger; Christopher W. Woodall; Steven McNulty; Carl Trettin; Justin Holgerson; Jingfeng Xiao (Ecology Letters, 2026)
Biodiversity can enhance forest resistance to drought, but the forms of diversity involved and conditions under which diversity confers resistance remain unclear. We used Forest Inventory and Analysis (FIA) plot data to examine whether four variables—structural richness (variation in tree heights, stand density, canopy cover and/or spatial heterogeneity), species richness (number of tree species), structural evenness and species evenness—are associated with the resistance of net primary productivity to drought and whether these relationships change with drought severity and by ecoregion. Structural richness was positively associated and species evenness was negatively associated with resistance, but the strength of these relationships varied by ecoregion. Relationships between structural richness and resistance and between species evenness and resistance became stronger under more severe droughts, supporting the stress gradient hypothesis. Forest managers cannot readily change abiotic conditions but could increase structural richness and select certain species to enhance forest resistance to drought.

Impacts of sodium benzoate and lysozyme on nitrification performance and resistance genes: Acute effects of single and co-exposure at different concentrations - Feifei Gao; Jingfeng Gao; Yameng Wang; Yan Guo; Ke Li; Qiyue Zuo; Tianyi Lu (Journal of Hazardous Materials, 2026)

Short-chain per/polyfluoroalkyl substances alternatives enhance horizontal gene transfer risks in nitrification systems under quaternary ammonium compounds antimicrobials co-stress despite lower acute toxicity than perfluorooctanoic acid - Hanyi Wang; Jingfeng Gao; Yingchao Cui; Yuxuan Wang; Yi Guo; Hao Chen (Water Research, 2025)

In-depth deciphering of partial sulfur autotrophic denitrification: Strategic S/N control and mechanistic interplay of Zn and dialkyldimethylammonium compounds on system performance and resistance genes transmission - Yukun Yuan; Jingfeng Gao; Zhiqi Wang; Yi Guo; Hongxin Xu; Liqin Zeng; Yifan Zhao (Chemical Engineering Journal, 2025)

Radical-free ultra-rapid disinfection: Application of the periodate/Mn(II) system in eliminating antibiotic-resistant bacteria and genes and degrading emerging contaminants - Yameng Wang; Jingfeng Gao; Yan Guo; Lei Wei; Ying Liu; Feifei Gao; Qiyue Zuo; Ke Li (Journal of Hazardous Materials, 2025)

Disinfectants induce divergent metabolism mechanisms in different partial nitrification-anammox coupled denitrification systems: Energy transformation and microbial stress response - Yi Guo; Jingfeng Gao; Hanyi Wang; Tian Xie; Ke Zhang (Journal of Hazardous Materials, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Preservatives induced succession of microbial communities and proliferation of resistance genes within biofilm and plastisphere in sulfur autotrophic denitrification system - Ke Zhang; Jingfeng Gao; Jinming Zhang; Yuxuan Wang; Hanyi Wang; Yi Guo; Tianyi Lu (Journal of Hazardous Materials, 2025)

Accelerated start-up of partial nitrification-anammox in municipal wastewater: Contributions by compound inhibitors and pyrite - Yingchao Cui; Jingfeng Gao; Yi Guo; Liqin Zeng; Jiawen An; Hanyi Wang (Journal of Environmental Management, 2025)

Meta-Analysis of the Effects of Cognitive Behavioral Therapy on Dietary Habits and Emotional Outcomes in Patients With Obesity Undergoing Metabolic and Bariatric Surgery - Haowen Gao; Guiqi Wang; Xinxin Zhang; Haobing Guo; Liyun Pang; Jingfeng Gu (Journal of Nutrition Education and Behavior, 2025)

Disinfectant-driven selective gene expression and metabolic evolution: Unstable nitrite accumulation and enhanced anammox activity in mixotrophic partial denitrification/anammox system - Yi Guo; Jingfeng Gao; Yi Zhang; Tian Xie; Hongxin Xu; Yuxuan Wang (Journal of Hazardous Materials, 2025)

Responses mechanisms of resistance genes in partial nitrification and anammox system under single and combined exposure to polystyrene nanoplastics and dodecyl dimethyl benzyl ammonium chloride - Yi Zhang; Jingfeng Gao; Yi Guo; Ying Liu; Tian Xie; Hongxin Xu; Hanyi Wang (Chemical Engineering Journal, 2025)

Supergravity separation: An innovative strategy for efficient cleaning and upgrading of coal gasification slag waste - Hailong Tang; Jingfeng He; Lixiang Fu; Jiahui Zhang; Liangyu Yao; Bin Yang; Lingtao Zhu; Shihai Guo (Waste Management, 2025)

Heat Deficit for Vegetation Leaf Senescence and Its Key Accumulation Process and Determinants at Northern Middle and High Latitudes During 2001–2022 - Zhihui Yuan; Gang Bao; Fei Li; Jiquan Chen; Jingfeng Xiao; Qier Mu; Enliang Guo; Siqin Tong; Sainbuyan Bayarsaikhan (Global Ecology and Biogeography, 2025)
Aim Cold degree days (CDD) represent the heat deficit for vegetation leaf senescence in autumn and serve as a critical parameter in modelling leaf senescence. This study aimed to quantify the spatiotemporal patterns of CDD and its key accumulation processes and determinants. Location At northern middle and high latitudes (> 30° N). Period 2001–2022. Major Taxa Studied Vegetation. Methods We estimate CDD as the cumulative sum of the difference between the daily mean temperature and a threshold temperature (12.75°C) during the period from midsummer to the end of the growing season. To identify its crucial metric, we employ a combination of grey relational analysis, random forest model and partial correlation analysis. Results The average CDD increases linearly with latitude at a rate of 5.9°C‐days per degree. Higher latitudes exhibit larger CDD (> 300.0°C‐days), longer accumulation periods (> 70 days) and faster accumulation rates (> 6.0°C/day), whereas lower latitudes show smaller CDD ( 46% of the study area, especially at high latitudes and on the Tibetan Plateau. While climate warming generally reduces CDD, an increase in precipitation frequency can counteract this trend and shape the relationship between precipitation amount and CDD. The effects of radiation and wind speed on CDD were less pronounced than those of precipitation frequency, with wind exerting a positive (cooling) effect that increases CDD accumulation and radiation producing a negative (heating) effect that decreases CDD accumulation. Main Conclusions This study highlights the critical aspects of the CDD accumulation process and emphasises the importance of incorporating precipitation frequency into CDD‐based autumn phenology models across northern latitudes.

Unignorable environmental risks: Insight into differential responses between biofilm and plastisphere in sulfur autotrophic denitrification system upon exposure to quaternary ammonium compounds - Yuxuan Wang; Jingfeng Gao; Zhiqi Wang; Yifan Zhao; Hanyi Wang; Yi Guo; Yukun Yuan; Hao Chen (Journal of Hazardous Materials, 2025)

Relic DNA obscures bacterial diversity and interactions in ballast tank sediment - Zhaozhao Xue; Haoze He; Yangchun Han; Wen Tian; Shengjie Li; Jingfeng Guo; Pei Yu; Lina Qiao; Wei Zhang (Environmental Research, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Experimental and numerical study on the flexural performance of composite beams with channel-section steel girder under fire exposure - Yong Liu; Qiuyu Xu; Lanhui Guo; Jingfeng Wang (Engineering Structures, 2025)

Phenacetin enhanced the inorganic nitrogen removal performance of anammox bacteria naturally in-situ enriched system - Yi Zhang; Jingfeng Gao; Jingqiang Zhao; Yifan Zhao; Ying Liu; Yi Guo; Tian Xie (Science of The Total Environment, 2024)

Environmental RNA metabarcoding for ballast water microbial diversity: Minimizing false positives - Zhaozhao Xue; Wen Tian; Yangchun Han; Shengjie Li; Jingfeng Guo; Haoze He; Pei Yu; Wei Zhang (Science of The Total Environment, 2024)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Will the removal of carbon, nitrogen and mixed disinfectants occur simultaneously: The key role of heterotrophic nitrification-aerobic denitrification strain - Yi Guo; Jingfeng Gao; Yi Zhang; Tian Xie; Qian Wang; Jiawen An (Journal of Hazardous Materials, 2024)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Seismic behavior of CFDST frame with metallic dampers: Damage-controlled design and performance assessment - Lei Guo; Jingfeng Wang; Wanqian Wang; Qingsong Guan (Soil Dynamics and Earthquake Engineering, 2024)

Chloroxylenol was the last straw for mixed disinfectants in inhibiting the activity of the heterotrophic/sulfur autotrophic denitrification systems: Performance, microbial community and different fractions of resistance genes - Yi Guo; Jingfeng Gao; Yukun Yuan; Yuxuan Wang; Hanyi Wang (Chemical Engineering Journal, 2024)

An automatic tracking method for fruit abscission of litchi using convolutional networks - Tong Huang; Jingfeng Guo; Long Yu; Houbin Chen; Zuanxian Su; Yueju Xue (Computers and Electronics in Agriculture, 2024)

A machine learning scheme for estimating fine-resolution grassland aboveground biomass over China with Sentinel-1/2 satellite images - Huaqiang Li; Fei Li; Jingfeng Xiao; Jiquan Chen; Kejian Lin; Gang Bao; Aijun Liu; Guo Wei (Remote Sensing of Environment, 2024)

Natural pyrite and ascorbic acid co-enhance periodate activation for inactivation of antibiotic resistant bacteria and inhibition of resistance genes transmission: A green disinfection process dominated by singlet oxygen - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang; Jiawen An (Journal of Hazardous Materials, 2024)

Hormesis and synergistic effects of disinfectants chloroxylenol and benzethonium chloride on highly efficient heterotrophic nitrification-aerobic denitrification functional strain: From performance to mechanism - Yi Guo; Jingfeng Gao; Yingchao Cui; Yifan Zhao; Biao Ma; Liqin Zeng; Hao Chen (Journal of Hazardous Materials, 2024)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

Phenacetin promoted the rapid start-up and stable maintenance of partial nitrification: Responses of nitrifiers and antibiotic resistance genes - Yi Zhang; Zejie Wu; Yongqing Gao; Jingfeng Gao; Fangbo Bao; Yifan Zhao; Yi Guo; Ying Liu (Science of The Total Environment, 2024)

Response of nitrification system to co-exposure of sucralose and single or combined disinfectants: Reducing damage to nitrification performance and aggravating the spread of intracellular resistance genes - Liqin Zeng; Jingfeng Gao; Yingchao Cui; Yifan Zhao; Yi Guo; Yukun Yuan; Hongxin Xu (Chemical Engineering Journal, 2024)

The synergistic effect of periodate/ferrate (VI) system on disinfection of antibiotic resistant bacteria and removal of antibiotic resistant genes: The dominance of Fe (IV)/Fe (V) - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Lei Wu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang (Journal of Hazardous Materials, 2024)

Identification of acetaminophen degrading microorganisms in mixed microbial communities using 13C-DNA stable isotope probing - Yingchao Cui; Jingfeng Gao; Yongqing Gao; Fangbo Bao; Yi Guo; Liqin Zeng; Hongxin Xu; Jiawen An (Chemical Engineering Journal, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Polymer surfactants as viscosity reducers for ultra-heavy oil: Synthesis and viscosity reduction mechanism - Xiaojun Zhang; Jixiang Guo; Dongtao Fei; Li Wang; Zhongying Peng; Jianmin Li; Jingfeng Dong (Fuel, 2024)

MHY1485 promotes adriamycin sensitivity in HepG2 cells by inhibiting autophagy - Jingfeng Guo; Yingying Lei; Liwei Liu; Zhenzhen Wen; Bo Zhang; Jincun Fang; Guohui Liang; Qikun Guo; Jing Peng (Functional & Integrative Genomics, 2024)

Plant community diversity alters the response of ecosystem multifunctionality to multiple global change factors - Zhenwei Xu; Xiao Guo; Warwick J. Allen; Xiaona Yu; Yi Hu; Jingfeng Wang; Mingyan Li; Weihua Guo (Global Change Biology, 2024)
Biodiversity is considered important to the mitigation of global change impacts on ecosystem multifunctionality in terrestrial ecosystems. However, potential mechanisms through which biodiversity maintains ecosystem multifunctionality under global change remain unclear. We grew 132 plant communities with two levels of plant diversity, crossed with treatments based on 10 global change factors (nitrogen deposition, soil salinity, drought, plant invasion, simulated grazing, oil pollution, plastics pollution, antibiotics pollution, heavy metal pollution, and pesticide pollution). All global change factors negatively impacted ecosystem multifunctionality, but negative impacts were stronger in high compared with low diversity plant communities. We explored potential mechanisms for this unexpected result, finding that the inhibition of selection effects (i.e., selection for plant species associated with high ecosystem functioning) contributed to sensitivity of ecosystem multifunctionality to global change. Specifically, global change factors decreased the abundance of novel functional plants (i.e., legumes) in high but not low diversity plant communities. The negative impacts of global change on ecosystem multifunctionality were also mediated by increased relative abundance of fungal plant pathogens (identified from metabarcoding of soil samples) and their negative relationship with the abundance of novel functional plants. Taken together, our experiment highlights the importance of protecting high diversity plant communities and legumes, and managing fungal pathogens, to the maintenance of ecosystem multifunctionality in the face of complex global change.

Different fates of extracellular and intracellular antibiotic resistance genes in flocs, granular and biofilm nitrification systems under the stress of acetaminophen - Yingchao Cui; Jingfeng Gao; Liqin Zeng; Yi Guo; Hongxin Xu; Mingyan Zhao (Journal of Hazardous Materials, 2024)

Fates of extracellular and intracellular antibiotic resistance genes in activated sludge and plastisphere under sulfadiazine pressure - Zhiqi Wang; Jingfeng Gao; Yifan Zhao; Yi Guo; Yi Zhang; Yukun Yuan; Mingyan Zhao; Liqin Zeng (Water Research, 2023)

The occurrence, ecological risk, and control of disinfection by-products from intensified wastewater disinfection during the COVID-19 pandemic - Bin Xue; Xuan Guo; Jinrui Cao; Shuran Yang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Science of The Total Environment, 2023)

Dynamics and biophysical controls of nocturnal water loss in a winter wheat-summer maize rotation cropland: a multi-temporal scale analysis - Xiaonan Guo; Jingfeng Xiao; Tianshan Zha; Guofei Shang; Peng Liu; Chuan Jin; Yucui Zhang (Agricultural and Forest Meteorology, 2023)

Hybrid simulation test and seismic assessment of CFDST moment resisting frame - Lei Guo; Jingfeng Wang; Wanqian Wang; Fei Lu; Hanlan Wang (Engineering Structures, 2023)

AIEgen-based nanotherapeutic strategy for enhanced FLASH irradiation to prevent tumour recurrence and avoid severe side effects - Meng Lyu; Tianfu Zhang; Yang Li; Jingfeng Xiang; Daoming Zhu; Ligang Xia; Bin Guo; Youhua Xu; Haijun Yu; Benzhong Tang (Chemical Engineering Journal, 2023)

Exploring the bacterial diversity and composition with special emphasis on pathogens in ship ballast water and sediments using full-length 16S rRNA gene sequencing - Tingxuan An; Xiaolan Lu; Yangchun Han; Chong Guo; Jingfeng Guo; Guorong Zhu; Wen Tian; Baoyi Lv (Marine Pollution Bulletin, 2023)

The knock-on effects of different wastewater feeding modes: Change in microbial communities versus resistance genes in pilot-scale aerobic sludge granulation reactors - Yi Guo; Dingchang Li; Yongqing Gao; Jingfeng Gao; Shujun Zhang; Fangbo Bao (Science of The Total Environment, 2023)

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

Seismic design and hybrid simulation test of existing concrete frames upgraded by metallic damper - Lei Guo; Jingfeng Wang; Hanlan Wang (Engineering Structures, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

Deciphering the interaction impacts between antiseptic benzethonium chloride and biofilm nitrification system: Performance, resistance mechanisms and biodegradation - Yingchao Cui; Jingfeng Gao; Mingyan Zhao; Yi Guo; Yifan Zhao; Zhiqi Wang (Water Research, 2023)

Growth of grasses and forbs, nutrient concentration, and microbial activity in soil treated with microbeads - Jingfeng Wang; Xiao Guo; Janice Brahney; Zhenwei Xu; Yi Hu; Wenyi Sheng; Yanni Chen; Mingyan Li; Weihua Guo (Environmental Pollution, 2023)

Mitigating the inhibition of antibacterial agent chloroxylenol on nitrification system-The role of Rhodococcus ruber in a bioaugmentation system - Yi Guo; Jingfeng Gao; Yifan Zhao; Ying Liu; Mingyan Zhao; Ziqiao Li (Journal of Hazardous Materials, 2023)

Development of hysteretic model for LEM-filled CFS shear walls under cyclic loading - Wanqian Wang; Jingfeng Wang; Lei Guo; Peifang Hu (Engineering Structures, 2023)

Surface modification to enhance the decarbonization performance of coal-series kaolin by triboelectric separation - Jingfeng He; Xin Zhang; Qiang Bai; Shibo Huang; Hao Chen; Chengjing Guo; Lingtao Zhu; Bin Yang (Applied Clay Science, 2023)

Work along both lines: The p-chloro-m-cresol achieved stable and long-term partial nitrification and inhibited the enrichment of resistance genes - Yi Guo; Jingfeng Gao; Zejie Wu; Ziqiao Li; Yi Zhang; Haoran Zhang (Chemical Engineering Journal, 2023)

Inhibition of Nitrospira and Nitrotoga by paracetamol achieved the rapid start-up and long-term stable operation of partial nitrification for low-strength ammonium wastewater - Yingchao Cui; Jingfeng Gao; Zejie Wu; Zhiqi Wang; Yifan Zhao; Yi Guo (Chemical Engineering Journal, 2023)

Different acesulfame potassium fate and antibiotic resistance propagation pattern in nitrifying and denitrifying sludge systems - Ziqiao Li; Jingfeng Gao; Yifan Zhao; Zhiqi Wang; Yingchao Cui; Dingchang Li; Yi Guo; Zejie Wu; Liqin Zeng (Science of The Total Environment, 2023)

Cation-π interaction in Mg(OH)2@GO-coated activated carbon fiber cloth for rapid removal and recovery of divalent metal cations by flow-through adsorption - Xiao Wang; Jingfeng Li; Qiang Guo; Menglan Xu; Xiaohan Zhang; Tong Li (Resources, Conservation and Recycling, 2023)

Efficient recovery of valuable metals from waste printed circuit boards via ultrasound-enhanced flotation - Linghua Chen; Jingfeng He; Lingtao Zhu; Qingyao Yao; Youbang Sun; Chengjing Guo; Hao Chen; Bin Yang (Process Safety and Environmental Protection, 2023)

A novel utilization of raw sepiolite: preparation of magnetic adsorbent directly based on sol–gel for adsorption of Pb(II) - Jiang Xu; Jingfeng He; Lingtao Zhu; Shulian Guo; Hao Chen (Environmental Science and Pollution Research, 2022)

Study on the effects of the different polar group of EPA-enriched phospholipids on the proliferation and apoptosis in 95D cells - Yao Guo; Qin Zhao; Yingying Tian; Yuanyuan Liu; Ziyi Yan; Changhu Xue; Jingfeng Wang (Marine Life Science & Technology, 2021)
EPA-enriched phosphatidylcholine (EPA-PC) and EPA-enriched phosphatidylethanolamine (EPA-PE) are newly identified marine phospholipids. The polar group of phospholipids is known to influence EPA-phospholipid activity. However, the differences in anti-tumor effects between EPA-PC and EPA-PE have not been reported. In this study, we evaluated the effects of two forms of EPA on the proliferation and apoptosis in the lung-cancer cell line 95D as well as possible molecular mechanisms. Our results showed that EPA-PC effectively inhibited proliferative activity and promoted apoptosis of 95D cells in a dose-dependent manner, while EPA-PE had no effect on cell proliferation, although it slightly promoted apoptosis. Western blot results showed that EPA-PC and EPA-PE upregulated the expression of PPARγ, RXRα, and PTEN, and downregulated the PI3K/AKT signaling pathway. Furthermore, EPA-PC and EPA-PE induced the expression of the pro-apoptotic gene, Bax, and reduced the expression of the anti-apoptotic gene, Bcl-xl. Additionally, EPA-PC and EPA-PE promoted the release of cytochrome c and activated the apoptotic enzyme-cleaved caspase-3. These data suggest that the anti-tumor effect of EPA-phospholipids may be exerted via a PPARγ-related mechanism. EPA-PC was more efficacious as compared to EPA-PE, which might be due to the different polar groups of phospholipids.

Perfusion microvessel density in the cerebral cortex of septic rats is negatively correlated with endothelial microparticles in circulating plasma - Zhenzhou Wang; Jingfeng Liu; Xi Liu; Xinjie Guo; Tian Li; Ran Pang; Meili Duan (Metabolic Brain Disease, 2021)

Detection and characterization of Aeromonas salmonicida subsp. salmonicida infection in crucian carp Carassius auratus - Zhengyi Lian; Jie Bai; Xiucai Hu; Aijun Lü; Jingfeng Sun; Yongjun Guo; Yajiao Song (Veterinary Research Communications, 2020)

Histochemical distribution of four types of enzymes and mucous cells in the intestine of koi carp (Cyprinus carpio var. koi) - Jingfeng Sun; Yize Wang; Aijun Lv; Jian-An Xian; Qingkui Wang; Shulin Zhang; Yongjun Guo; Kezhi Xing (Fish Physiology and Biochemistry, 2019)

Removal of hexavalent chromium from water by modified sponge iron particles and insights into mechanism - Guilin Zhu; Junde Song; Weihong Dong; Jingfeng Lu; Yan Wang; Weinan Jiang; Ping Guo (Environmental Science and Pollution Research, 2018)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)

Green Synthesis of Oxovanadium(IV)/chitosan Nanocomposites and Its Ameliorative Effect on Hyperglycemia, Insulin Resistance, and Oxidative Stress - Yanjun Liu; Xu Jie; Yongli Guo; Xin Zhang; Jingfeng Wang; Changhu Xue (Biological Trace Element Research, 2016)

Preparation of Triacylglycerols Enriched in DHA from Single Cell Glycerides via Molecular Distillation and Enzymatic Glycerolysis - Zhaomin Sun; Lu Yang; Changhu Xue; Zhengxia Guo; Haihua Cong; Yuming Wang; Yong Xue; Jingfeng Wang (Journal of Aquatic Food Product Technology, 2015)